A Network Meta-Analysis of Efficacy and Evaluation of Safety of Subcutaneous Pegylated Interferon Beta-1a versus Other Injectable Therapies for the Treatment of Relapsing-Remitting Multiple Sclerosis. - Keith Tolley; Michael Hutchinson; Xiaojun You; Ping Wang; Bjoern Sperling; Ankush Taneja; Mohammed Kashif Siddiqui; Elizabeth Kinter (PLoS ONE)
Subcutaneous pegylated interferon beta-1a (peginterferon beta-1a [PEG-IFN]) 125 μg every two or four weeks has been studied in relapsing-remitting multiple sclerosis (RRMS) patients in the pivotal Phase 3 ADVANCE trial. In the absence of direct comparative evidence, a network meta-analysis (NMA) was conducted to provide an indirect assessment of the relative efficacy, safety, and tolerability of PEG-IFN versus other injectable RRMS therapies. Systematic searches were conducted in MEDLINE, Embase, and the Cochrane Library, and conference proceedings from relevant annual symposia were hand-searched. Included studies were randomized controlled trials evaluating ≥1 first-line treatments including interferon beta-1a 30, 44, and 22 μg, interferon beta-1b, and glatiramer acetate in patients with RRMS. Studies were included based on a pre-specified protocol and extracted by a team of independent reviewers and information scientists, utilizing criteria from NICE and IQWiG. In line with ADVANCE findings, NMA results support that PEG-IFN every 2 weeks significantly reduced annualized relapse rate, and 3- and 6-month confirmed disability progression (CDP) versus placebo. There was numerical trend favoring PEG-IFN every 2 weeks versus other IFNs assessed for annualized relapse rate, and versus all other injectables for 3- and 6-month CDP (6-month CDP was significantly reduced versus IFN beta-1a 30 μg). The safety and tolerability profile of PEG-IFN beta-1a 125 μg every 2 weeks was consistent with that of other evaluated treatments. Study limitations for the NMA include variant definitions of relapse and other systematic differences across trials, assumptions that populations were sufficiently similar, and inability to perform NMA of adverse events. With similar efficacy compared to other RRMS treatments in terms of annualized relapse rate and 3- and 6-month CDP, a promising safety profile, and up to 93% reduction in number of injections (which may improve adherence), PEG-IFN every 2 weeks offers a valuable alternative treatment option for patients with RRMS.